2018
DOI: 10.3171/2017.6.jns17130
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting reoperation of chronic subdural hematoma following primary surgical evacuation

Abstract: OBJECTIVE Chronic subdural hematoma (CSDH) is commonly encountered in neurosurgical practice. However, surgical evacuation remains complicated by a high rate of reoperation. The optimal surgical approach to reduce the reoperation rate has not been determined. In the current study, the authors evaluated the prognostic value of clinical and radiographic factors to predict reoperation in the context of CSDH. METHODS A retrospective review of 325 CSDH patients admitted to an academic medical center in the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 28 publications
2
81
3
1
Order By: Relevance
“…CSDH is one of the most commonly treated neurosurgical disorders and BHD is a universal surgical treatment [11,18,27]. The rate of CSDH recurrence following BHD is 4-38% and the complications rate is 0-38% [6-12, 24, 26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSDH is one of the most commonly treated neurosurgical disorders and BHD is a universal surgical treatment [11,18,27]. The rate of CSDH recurrence following BHD is 4-38% and the complications rate is 0-38% [6-12, 24, 26].…”
Section: Discussionmentioning
confidence: 99%
“…BHD is the most widely used technique, and has a satisfactory outcome, but has a CSDH recurrence rate of 4-38% [6][7][8][9][10][11][12]. Several studies have revealed that predictors of CSDH recurrence following surgical evacuation include age, sex, antiplatelet or anticoagulation therapy, Glasgow Coma Scale (GCS), diabetes mellitus, hypertension, bilateral hematoma, preoperative hematoma size, midline shift, hematoma density, intraoperative irrigation, type of surgery and postoperative air collection, however, these results are inconsistent [7,[13][14][15][16][17][18][19]. The more controversial risk factors include surgery type and intraoperative irrigation [9,10,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Although we used endoscopic surgery in all types of CSDH, patients with a higher risk of recurrence could be good candidates for such procedures. Patients on antiplatelet therapy, 51,52 organized hematoma, 53 solid clot, [53][54][55] large size hematomas, 56 CSDH with thick membrane, 57,58 septate hematomas, 52,59,60 a lesser percentage of hematoma drainage, 52,55 more postoperative air in the hematoma cavity, 61,62 and recurrent CSDH 21 are at high risk of recurrences. Such patients could benefit more by endoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 The best evidence, published in the systematic reviews of Malcolm et al and van de Vijfeijken et al, shows a higher failure risk in autologous bone than allografts, which brings to light synthetic implants and favors the decision to use them. 6,7 In this analysis, the significantly higher rates of reoperation in patients with autologous implants are primarily due to bone resorption. The factors that result in clinically relevant bone resorption remain unclear.…”
Section: Responsementioning
confidence: 98%